2005
DOI: 10.1111/j.1744-7429.2005.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Massive Destruction of Symphonia globulifera (Clusiaceae) Flowers by Central American Spider Monkeys (Ateles geoffroyi)1

Abstract: Although more than 39 primate species have been described as nectar feeders, no studies have documented the negative affect this behavior may have on the reproductive success of the plants they consume. Here we report, for the first time, massive flower destruction of the tropical tree Symphonia globulifera by the frugivorous spider monkey, Ateles geoffroyi, and document the detrimental effect this behavior has on fruit set. Foraging behavior was collected from one troop of A. geoffroyi during 460 contact hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
(72 reference statements)
0
19
0
Order By: Relevance
“…Our knowledge of how plants respond to herbivory comes primarily from experiments focusing on damage to nonreproductive tissue, even though petal damage can be quite severe with large consequences for plant Wtness in some populations (Washitani et al 1996;Wolfe 2002;Riba-Hernandez and Stoner 2005). In this study, I showed that both natural and artiWcial damage to reproductive tissues resulted in a variety of negative Wtness eVects in N. menziesii, but with little evidence of indirect eVects of damage.…”
Section: Discussionmentioning
confidence: 88%
“…Our knowledge of how plants respond to herbivory comes primarily from experiments focusing on damage to nonreproductive tissue, even though petal damage can be quite severe with large consequences for plant Wtness in some populations (Washitani et al 1996;Wolfe 2002;Riba-Hernandez and Stoner 2005). In this study, I showed that both natural and artiWcial damage to reproductive tissues resulted in a variety of negative Wtness eVects in N. menziesii, but with little evidence of indirect eVects of damage.…”
Section: Discussionmentioning
confidence: 88%
“…is a particularly interesting subject for investigating the evolution and adaptive value of trichromacy for frugivory in platyrrhine monkeys because it is highly frugivorous (spending 57-77% of feeding time on fruits), and prefers ripe fruits over other food items [Chapman, 1987;Riba-Hernández & Stoner, 2005;Symington, 1988]. In addition, Ateles spp.…”
Section: Introductionmentioning
confidence: 99%
“…For example, spider monkeys ( Ateles geoffroyi ) limit the fruit set of Symphonia globulifera by eating its flowers (Riba-Hernandez and Stoner, 2005). For three months S. globulifera flowers represented between 86 to 100% of a study groups monthly foraging time, resulting in the complete detachment of flowers in 80% of their feeding episodes.…”
Section: Discussionmentioning
confidence: 99%